Renacer: analysis of a journal from the bolivian comunity in Argentina - Gerardo Halpern; Luciano Beccaría (Estudos em Comunicação, 2012)
The present work analyzes the construction of Renacer, a signiﬁcant graphic communication production of the so-called “Bolivian community in Argentina”. This newspaper, which has reached its twelfth year of existence and uninterrupted circulationin the City of Buenos Aires, goes beyond the traditional newspaper format to inscribe itself within a matrix of construction of the identity of Bolivian migrants in Argentina. This matrix, far from expressing the Argentine hegemonic logic around regional immigration in general and Bolivian migrants in particular (homogeneity, passivity, docility, foreignness, etc.), exposes the complexity of immigration and its identiﬁcations. Renacer also entails certain theoretical challenges for the Communication Sciences and Anthropology as it reveals the political intervention of a poliphony that has been denied, hidden or repressed throughout the history of Argentina. This polyphony expresses the community complexities and heterogeneities that dispel the homogeneity and essentiality attributed to the identity while forcing the approach from its inherent diversity, conﬂictivity and politics. By circumscribing the analysis to the ﬁrst decade of the 21st century – a stage of signiﬁcant transformations in Bolivia and Argentina – we attempt to establish how Renacer serves as tool for (and is the expression of) the dispute over meanings within the migrant group and for the legitimization of their political positioning in the public sphere.